2018
DOI: 10.1007/s10658-018-1438-3
|View full text |Cite
|
Sign up to set email alerts
|

Pectobacterium carotovorum subsp. brasiliense and Pectobacterium carotovorum subsp. carotovorum as causal agents of potato soft rot in Algeria

Abstract: During surveys carried out in 2014 and 2015 in Algerian potato fields, severe bacterial tuber soft rot was observed. Twenty-one Gram-negative pectinolytic bacterial isolates were obtained from diseased potato tubers. These induced a hypersensitive reaction and soft rot symptoms when inoculated in tobacco leaves and potato tubers, respectively. PCR amplification using the Y1/Y2 primers demonstrated that all of the bacterial isolates belonged to the genus Pectobacterium. Phylogenetic analysis using partial malat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 53 publications
(64 reference statements)
0
19
0
1
Order By: Relevance
“…The international distribution of the genus Pectobacterium increases concerns about the economic losses caused by this bacterium to the potato growers. A study in the neighboring country Algeria, carried out between 2014 and 2015, revealed the presence of pectinolytic bacteria causing soft rot in potatoes that belonged to P. brasiliense and P. carotovorum , as judged by MLSA [ 63 ]. Ozturk et al reported the presence of P. atrosepticum , P. brasiliense , P. carotovorum and P. parmentieri species in Turkey [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The international distribution of the genus Pectobacterium increases concerns about the economic losses caused by this bacterium to the potato growers. A study in the neighboring country Algeria, carried out between 2014 and 2015, revealed the presence of pectinolytic bacteria causing soft rot in potatoes that belonged to P. brasiliense and P. carotovorum , as judged by MLSA [ 63 ]. Ozturk et al reported the presence of P. atrosepticum , P. brasiliense , P. carotovorum and P. parmentieri species in Turkey [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pectobacterium brasiliense (Pbr) is a worldwide-distributed bacterial plant pathogen causing soft rot of a wide range of economically important crops. Pbr has been reported in Eurasia: from Western European countries to Russia and China [ 4 , 5 , 6 ], in Africa: South Africa, Morocco, Algeria and Kenya [ 7 , 8 , 9 , 10 ]. Pbr has been constantly reported since 2004 causing significant losses particularly of potato ( Solanum tuberosum L.) [ 11 , 12 , 13 , 14 ] and posing a threat to worldwide potato gross production value which is estimated to be $63914 million in 2018 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, severe wet rot (tip over) in banana plants caused by Pcc was recorded in greenhouses in Turkey (Basim et al, 2019). Pcc is also a major pathogen of tuber soft rot in different countries and results in severe economic losses (Muturi et al, 2018;Naas et al, 2018).…”
Section: Introductionmentioning
confidence: 99%